ECCO Guidelines on Therapeutics in Crohn's Disease: Surgical Treatment - Adamina, Michel; Minozzi, Silvia; Warusavitarne, Janindra; Buskens, Christianne Johanna; Chaparro, Maria; Verstockt, Bram; Kopylov, Uri; Yanai, Henit; Vavricka, Stephan R.; Sigall-Boneh, Rotem; Sica, Giuseppe S.; Reenaers, Catherine; et al. (Journal of Crohns & Colitis, 2024)
This article is the second in a series of two publications on the European Crohn's and Colitis Organisation [ECCO] evidence-based consensus on the management of Crohn's disease. The first article covers medical management; the present article addresses surgical management, including preoperative aspects and drug management before surgery. It also provides technical advice for a variety of common clinical situations. Both articles together represent the evidence-based recommendations of the ECCO for Crohn's disease and an update of prior ECCO Guidelines.
CRIS-Team Scopus Importer:2024-10-25
Keywords: Crohn’s disease; inflammatory bowel disease [IBD]; surgery